The Impact of Sectors Performance and Quality of Institutions on Economic Volatility: In Case of Asia - Mujahid, Hira; Alam, Shaista (Asian Journal of Economic Modelling, 2020)
Asian countries contribute sixty percent of total world economic activity and also perform significant role in supporting the interconnected global economy. Therefore, growth of sectors in Asian economies such as agriculture, industry and services accounts major contribution in the global sectors growth. This study is one of very few studies which have investigated the relationship of agriculture, industry and services, institutional quality on economic volatility. The aim of this paper is to find the relationship between sectoral growth, economic growth and economic volatility for panel of Asian Economies This study contributes in the existing literature the association of quality of institutions with economic growth and the link of quality of institutions with economic volatility. For this purpose, study compiles a panel of 47 Asian economies with the time span of 1996-2016 and applied Fixed and Random effect model on selected countries. The paper’s primary contribution is finding that that the growth of agricultural and industrial sector’s increase the economic volatility and significant effect. However, the growth in agriculture and service sector have significant effect on the growth of Asian economy. The paper documents that the economic volatility depends on sectoral growth, institutions performance, trade openness and financial development. The agriculture and service sector growth of the Asian economies significant reduced economic volatility. To improve the growth of sectors; Skill formation in sectors, technological support, financing through advance methods are required.